Holmium-YAG Laser Ureteroscopic Lithotripsy in a Patient with Ectopic Malrotated Kidney - Razzaghi, Mohammad Reza; Mazloomfard, Mohammad Mohsen; Mohammadi, Reza; Bahrami-Motlagh, Hooman (Journal of Lasers in Medical Sciences, 2012)
The incidence of stone disease among patients with congenital renal anomalies including malrotated kidney is more than in normal population due to poor urine drainage and stasis (1). Various minimally invasive options have been used for the management. Ureteroscopy and Holmium:YAG laser lithotripsy have been reported with favorable outcomes (2). We report a 30-year-old male who presented to our hospital having a right side malrotated kidney with a large stone in it. He underwent two session of ureteroscopy and Holmium:YAG laser lithotripsy